Changes in Microbial Safety and Quality of High-Pressure Processed Camel Milk - Tareq M. Osaili; Dinesh Kumar Dhanasekaran; Fayeza Hasan; Reyad S. Obaid; Anas A. Al-Nabulsi; Amin N. Olaimat; Leila Cheikh Ismail; Nadia Alkalbani; Mutamed Ayyash; Gafar Babatunde Bamigbade; Richard Holley; Adan Shahzadi Cheema; et al. (Foods)
High-pressure processing (HPP) is used as a non-thermal approach for controlling microbial viability. The purposes of this study were to (i) establish the decimal reduction times (D-values) for pathogenic bacteria during 350 MPa HPP treatment,; (ii) evaluate the impact of 350 MPa HPP on total plate count (TPC), yeasts and molds (YM), and lactic acid bacteria (LAB) in camel milk; (iii) investigate the behavior of several spoilage-causing bacteria during storage at 4 °C and 10 °C for up to 10 d post-HPP treatment; and (iv) assess the effect of HPP on the protein degradation of camel milk. The D-values for L. monocytogenes, E. coli O157:H7, and Salmonella spp. were 3.77 ± 0.36 min, 1.48 ± 0.08 min, and 2.10 ± 0.13 min, respectively. The HPP treatment decreased pathogenic microorganisms by up to 2 to 3 log cfu/mL (depending on treatment conditions). However, HPP reduced TPC, YM, and LAB by <1 log cfu/mL, regardless of the length of pressure exposure. HPP treatment, even at extended holding times, did not significantly alter either the proteolytic activity or casein micelle structure in camel milk. This study highlights HPP as a promising non-thermal technique for enhancing the microbiological safety of camel milk.